2021
DOI: 10.15585/mmwr.mm7011e1
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in COVID-19 Incidence by Age, Sex, and Period Among Persons Aged <25 Years — 16 U.S. Jurisdictions, January 1–December 31, 2020

Abstract: The COVID-19 pandemic has disproportionately affected racial and ethnic minority groups in the United States. Whereas racial and ethnic disparities in severe COVID-19-associated outcomes, including mortality, have been documented (1-3), less is known about populationbased disparities in infection with SARS-CoV-2, the virus that causes COVID-19. In addition, although persons aged <30 years account for approximately one third of reported infections, § there is limited information on racial and ethnic disparities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 10 publications
4
68
0
Order By: Relevance
“…This attenuation in disparities appears to be due, at least in part, to a stronger relative increase in the test positivity percentage among White individuals over time rather than a decline in test positivity among racial and ethnic minority groups, which is likely driven by the pandemic generalizing from diverse metropolitan areas to less diverse rural areas. 4,5,8 Our findings on disparities for testing positive among Black and Hispanic individuals in the first months of the pandemic have been demonstrated previously. [1][2][3][4][5] This study extended previously published models to evaluate patterns in disparities over the first full year of the pandemic.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This attenuation in disparities appears to be due, at least in part, to a stronger relative increase in the test positivity percentage among White individuals over time rather than a decline in test positivity among racial and ethnic minority groups, which is likely driven by the pandemic generalizing from diverse metropolitan areas to less diverse rural areas. 4,5,8 Our findings on disparities for testing positive among Black and Hispanic individuals in the first months of the pandemic have been demonstrated previously. [1][2][3][4][5] This study extended previously published models to evaluate patterns in disparities over the first full year of the pandemic.…”
Section: Discussionsupporting
confidence: 78%
“…[4][5][6][7] Recently, additional analyses have suggested that racial and ethnic disparities may be changing over time as outbreaks spread from racially and ethnically diverse metropolitan centers to more rural and less diverse areas. 4,5,8 In this report, we updated our previous analyses 4,5 to evaluate changes in disparities for testing positive with SARS-CoV-2 over the first full year of the pandemic and by geographic region in the largest integrated healthcare system in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, in NSSP, Native Hawaiian and Other Pacific Islander (NH/PI) and Asian are separate categories. However, these groups were combined in the population estimates used, so these groups were combined into A/PI for this analysis, likely masking previously reported COVID-19 disparities among NH/PI persons (3). Race/ethnicity-specific estimates for non-Hispanic persons of multiple and other races were not calculated because population denominators were unavailable.…”
Section: What Is Added By This Report?mentioning
confidence: 99%
“…This slight underrepresentation might be because of several factors including disparities in access to health care and testing [26]. However, Hispanic or Latino ethnicity was associated with increased odds of hospitalization, consistent with reports highlighting the disproportionate impact of COVID-19 on the Hispanic or Latino population in the United States [27,28].…”
Section: Plos Onesupporting
confidence: 79%